Popular Financial Report - Dublin 2023 (European journal of volunteering and community-based projects, 2024)
The 2023 Popular Financial Report (PFR) for Dublin presents a clear and accessible overview of the city’s financial status, aiming to promote transparency and engagement with residents and stakeholders. This report summarizes Dublin's revenue sources, including property taxes, grants, and service fees, alongside expenditures across key areas such as housing, public infrastructure, environmental sustainability, and community programs. The PFR highlights significant investments in affordable housing, transportation, and climate resilience, aligning with Dublin's commitment to sustainable growth and enhanced quality of life. Through visuals and simplified financial data, the report provides insights into the city's budgeting priorities, resource allocation, and strategic initiatives, underscoring Dublin's progress toward social and economic goals. This document complements the Annual Financial Statement, making complex financial information understandable for the public and ensuring alignment with Dublin’s long-term vision for an inclusive, resilient, and thriving city.